An innovative green protocol for the quantification of benzothiazoles, benzotriazoles and benzosulfonamides in PM10 using microwave-assisted extraction coupled with solid-phase microextraction gas chromatography tandem-mass spectrometry. (15th September 2021) - Naccarato, Attilio; Tassone, Antonella; Martino, Maria; Elliani, Rosangela; Sprovieri, Francesca; Pirrone, Nicola; Tagarelli, Antonio
Abstract: Benzothiazoles (BTHs), benzotriazoles (BTRs), and benzenesulfonamides (BSAs) are chemicals used in several industrial and household applications. Despite these compounds are emerging pollutants, there is still a lack of information about their presence in outdoor air samples. In this paper, we developed a new method for the quantification of BTHs, BTRs, and BSAs in airborne particulate matter (PM10 ). The extraction of fourteen analytes from PM10 was accomplished by microwave-assisted extraction (MAE) using an environmentally friendly mixture of water and ethanol. SPME was used to analyze the target compounds from the MAE extract by gas chromatography-tandem mass spectrometry (SPME-GC-MS/MS), eliminating additional sample clean-up steps. The best working conditions for MAE and SPME were examined multivariately by experimental design techniques. The target compounds were quantified in selected reaction monitoring acquisition mode. The proposed method was carefully validated, and the achieved results were satisfactory in terms of linearity, lower limit of quantification (picograms per cubic meter), intra- and inter-day accuracy (81–118% and 82–114%, respectively), and precision (repeatability and reproducibility in the range 2.3–17% and 7.4–19%, respectively). The application in a real monitoring campaign showed that the developed protocol is a valuable and eco-friendly alternative to the methods proposed so far. Graphical abstract: Image 1 Highlights: A new method for BTHs, BTRs and BSAs analysis in airborne PM10 is presented. BTHs, BTRs and BSAs are extracted from PM10 by MAE. The method uses only a water/ethanol mixture in the whole procedure. The analytes are sampled by SPME without any clean-up step. MAE and SPME were optimized by experimental design.